PENGARUH KEPEMIMPINAN TERHADAP KINERJA PEGAWAI BIDANG TRANSMIGRASI PADA KANTOR DINAS TENAGA KERJA DAN TRANSMIGRASI PROVINSI MALUKU - Stevanus Johan Gomies; Cynthia Imelda Tjokro; Victorio Fernando Nahuway (P3M Politeknik Negeri Ambon, 2022)
In practice, at the office of the Office of Manpower and Transmigration for the Province of Maluku, there are still many problems found in the work of employees, even the work often makes mistakes many times. This is influenced by the leadership of the Head of Transmigration at the Office of Manpower and Transmigration in the Province of Maluku, the leadership still pays little attention to the work of employees and there is even a lack of control or supervision from the leadership of each employee's work, lack of firmness in fostering employees who are irresponsible to work, employees who are not disciplined with work time and work breaks. In the end the leadership affects the performance of employees.This study uses a quantitative approach because the data to be used to analyze the relationship between variables is expressed by numbers or a numerical scale (Kuncoro, 2003:41).According to Sugiyono (2012) the sample is part of the number of characteristics possessed by a certain population. The sampling method used is non-probability sampling with saturated sample techniques. Saturated sample is a sampling technique when all members of the population are used as samples. This is often done when the population is relatively small, less than 30 people, or research that wants to make generalizations with very small errors. So the number of samples in this study is 30 people according to the number of employees in the transmigration sector. Keywords: Leadership; Performance